ANALYSIS WIRETAPPING AUTHORITY UPPER KPK LAW ENFORCEMENT IN THE PERSPECTIVE OF HUMAN RIGHTS - Ariyanto Ariyanto (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Corruption still thrives in the country, if we listen to the news certainly no news about corruption in the bureaucracy in this country, reporting on corruption makes sad because it turns out the culprit educated and have a certain position in the structure of government, but so far the efforts of law enforcement do KPK to catch the perpetrators of corruption have yielded results, there are some major corruption cases were successfully handled by the KPK, the key to the success of the Commission in uncovering cases of corruption is the result of tapping , by tapping the Commission can uncover cases of corruption in the country. The Act authorizes the Commission to conduct wiretaps, as stipulated in article 12 paragraph (1) of Law No. 30 of 2002 on the Corruption Eradication Commission, through the authority of KPK tapping it makes corruption can be prosecuted Legally. However, on one hand, tapping Authority, has given the assumption that the wiretapping conducted by the Commission can be considered to violate human rights that violates a person's privacy. This study wants to answer: Does the wiretapping conducted by the Commission can be regarded as a violation of human rights? Does the eavesdropping law enforcement can be implemented by the Commission? Purpose of this study was to determine whether the wiretapping can be categorized can violate human rights, and Do by tapping enforcement efforts could implement by the Commission. The method used in this research is descriptive qualitative. This study concluded that the Authority Tapping the Commission do not constitute a violation of human rights, as is the procedure to conduct wiretaps are in accordance with the legal instruments in force, and besides tapping is done to satisfy the justice of the people who suffer as a result of behaviors corruption, by tapping also KPK can dismantle the big cases, so every year since the Commission established, there are cases of corruption revealed by the Commission, it is thus the rule of law for the perpetrators of corruption can be implemented. Keywords:Wiretapping Authority Commission, Law Enforcement, Human Rights